Gripping motion of artificial hand using EMG signal - Mat Rosly, Muhammad Hadi; Rahman, Md Mozasser (IEEE, 2016)
Electromyogram (EMG) generates small signal amplitude upon muscle contraction. It is difficult to distinguish the significance of its EMG response but yet its control feasibility has been proven by many research. In this paper, the feasibility of EMG based artificial hand utilizing conventional EMG sensor was put into study. Instead of performing complex processing which may exponentially increase the cost of EMG artificial hand, the concept proposed in this paper, utilizes simple threshold activation key. The rest of the control specification is dealt with force sensor feedback. From this study, it is proven that using conventional EMG sensor to control an artificial hand is feasible to perform simple task. However, further study is required to enhance the reliability of the system.